Electrostatic changes enabled the diversification of an exocyst subunit via protein complex escape - Concepción, Juan Carlos de la; Duverge, Héloïse; Kim, Yoonwoo; Julian, Jose; Xu, Haonan D.; Watt, Matthew N.; Ikene, Sara Ait; Bianchi, Anita; Grujic, Nenad; Papareddy, Ranjith; Grishkovskaya, Irina; Haselbach, David; et al. (Nature plants, 2025)
Protein neofunctionalization is a key driver of cellular complexity. However, subunits of multimeric protein complexes are often thought to be evolutionarily constrained, limiting their capacity for functional divergence. This presents a paradox in plants, where the Exo70 subunit of the exocyst—an octameric complex essential for exocytosis—has undergone striking expansion and diversification. Here we show that electrostatic changes in the N-terminal helix of Exo70 facilitated its physical and functional dissociation from the exocyst, relieving constraints imposed by complex integration. Using Marchantia polymorpha and Arabidopsis thaliana, we demonstrate that this ‘complex escape’ enables Exo70 paralogues to acquire distinct localizations, interactomes and functions independent of canonical exocytosis. Ancestral reconstructions across land plants reveal that this electrostatic shift predates the extensive radiation of the plant Exo70 protein family, with some lineages later reassociating with the complex. Our findings reveal a reversible mechanism that enabled Exo70 to circumvent the evolutionary and biophysical constraints imposed by complex integration and diversify—a mechanism that could represent a generalizable route to protein neofunctionalization and cellular innovation.
Online veröffentlicht: 31. Oktober 2025
Gesehen am 08.12.2025